Effects of Lidocaine-Mediated CPEB3 Upregulation in Human Hepatocellular Carcinoma Cell Proliferation In Vitro. (17th April 2018) - Liu, Hongjun; Wang, Yiru; Chen, Bing; Shen, Xia; Li, Wenxian
Abstract : Lidocaine displays antitumor activity by inducing apoptosis and suppressing tumor growth in human hepatocellular carcinoma (HepG2) cells in vitro. However, the molecular mechanism underlying lidocaine-mediated antitumor activity is unclear. In this study, HepG2 cells were treated with lidocaine, and cell proliferation and colony-forming ability were assessed. The expression level of cytoplasmic polyadenylation element binding protein 3 (CPEB3) was detected by real-time quantitative PCR and western blot. Lidocaine treatment resulted in decreased HepG2 cell viability and colony formation in a dose-dependent manner. In hepatocellular carcinoma patient samples, CPEB3 was downregulated and was associated with poor prognosis and high-grade malignancy. Additionally, CPEB3 was a critical mediator of lidocaine-induced repression of HepG2 cell proliferation. These results demonstrated that lidocaine decreased cell viability and colony-forming ability of HepG2 cells by upregulating CPEB3 expression.